Microstructural variations and kinetic behaviors during metadynamic recrystallization in a nickel base superalloy with pre-precipitated δ phase. (5th March 2019) - He, Dao-Guang; Lin, Y.C.; Wang, Li-Hua
Abstract: The metadynamic recrystallization (MDRX) features of a Ni-based alloy with pre-precipitated δ phases (Ni3 Nb) are researched by two-pass hot compressive experiments. Microstructural variations with deformation parameters are analyzed. Results reveal that the softening effects induced by MDRX become obvious at large first-pass strains, high strain rates or deformation temperatures, as well as the large percentage of pre-precipitated δ phase. At high deformation temperatures, the rearrange/annihilation of vacancies and dislocations are enhanced, which promotes the growth of substructures and the dissolution of δ phase. However, the coarsening of MDRX grains and the dissolution of δ phase become weaken with reducing the strain rate, first-pass strain or percentage of pre-precipitated δ phases. Considering the effects of pre-precipitated δ phases and deformation parameters on MDRX behavior, an improved kinetic model is proposed to predict the MDRX softening fractions. The forecasted results are well identical to the tested ones, which signifies the improved kinetic model can accurately evaluate the MDRX characteristics of the studied superalloy. Graphical abstract: Unlabelled Image Highlights: Metadynamic recrystallization (MDRX) features of a superalloy with pre-precipitated δ phases are researched. Softening effects induced by MDRX are sensitive to deformation parameters and pre-precipitated δ phase. Coarsening of MDRX grains and dissolution of δ phase become weaken with reducing pre-precipitated δ phase. An improved MDRX kinetic model is developed considering the effects of pre-precipitated δ phases.